Sweet Charity [videorecording (DVD)] - Fosse, Bob, 1927-1987; Fosse, Bob, 1927-1987; MacLaine, Shirley, 1934-; Montalbán, Ricardo; Davis, Sammy, Jr., 1925-1990; Fellini, Federico (Universal Studio, 2003)
A lovelorn New York dance hall hostess named Charity Hope Valentine dreams of old-fashioned romance but falls in love with one undeserving man after another.